Pengembangan Kompetensi Tajwid melalui Metode SQ (Shahibul Qur’an) bagi Pemula - Makhful Makhful; Havidz Cahya Pratama; Kusno Kusno; Suyadi Suyadi (Jurnal Surya Masyarakat, 2025)
Mastery of tajwid (rules of Quranic recitation) is a fundamental element in reading the Qur’an correctly. However, some members of Pemuda Muhammadiyah and Nasyiatul 'Aisyiyah in Rawalo Subdistrict, Banyumas, still face difficulties in reciting the Qur’an according to proper tajwid principles. This Community Service Program (PkM) aims to enhance tajwid competence through the Shahibul Qur’an (SQ) method—an interactive approach emphasizing talaqqi (direct instruction), repetition, and immediate feedback. The program involved 30 participants and was conducted through a series of activities: pre-test, training, guided simulation, and post-test. It adopted a Participatory Action Research (PRA) approach, positioning facilitators as reflective companions. Based on the initial survey, 70% of participants had not fully understood tajwid, and 80% had never been introduced to the SQ method. After the training, significant improvements were recorded: 90% of participants gained a better understanding of tajwid, 85% found the SQ method helpful, and 75% experienced increased confidence in teaching the Qur’an. Participants also showed high motivation and interest in using SQ as an alternative learning method. The method’s effectiveness was evident through improved articulation (makhraj), phonetic characteristics (sifat huruf), and accurate recitation via repetition. The training also fostered institutional support, including the establishment of new Qur’an learning centers (TPQ) initiated by local Muhammadiyah and Nasyiatul 'Aisyiyah cadres. This program is recommended to be implemented sustainably, with structured follow-up programs, funding support, reporting mechanisms, and expanded partnerships to optimize the broader impact of the SQ method on community-based Qur’anic education.